Characterization of Bacterial Mannanase for Hydrolyzing Palm Kernel Cake to Produce Manno-oligosaccharides Prebiotics - W Utami; A Meryandini; K G Wiryawan (Faculty of Animal Science, Bogor Agricultural University, 2013)
Palm kernel cake (PKC) is a promising source of prebiotics, since it contains high amount of β-mannan which can be further hydrolyzed to manno-oligasaccharides (MOS), a prebiotic. Therefore, this research was carried out to analyze the capability of a bacterial isolate (A2 isolates) previously isolated from soils sample from around IPB campus to hydrolyze PKC. Based on 16S-DNA analysis, isolate A2 was identified as Brevibacillus borstelensis. Mannanase of A2 isolate had an optimum condition at 90 oC and pH 7. Mannanase activity of crude extracts using Locust Bean Gum (LBG) and PKC as substrates were 0.37U/mL and 0.032U/mL, respectively. However, the most favorable production of oligosaccharides based on the degree of polymerization was obtained after 72-h of incubation with the ratio of substrate:enzyme, 1.2:1, on 1.5% PKC as substrate. The manno-oligosaccharides prebio-tic obtained was found to interfere the growth of both lactic acid bacteria (Lactobacillus casei) and pathogenic microflora (Escherichia coli). E. coli apparently could not use this prebiotic as the carbon sources, in contrast to L. casei. Substitution of carbon source in medium with prebiotics reduced the capability of L. casei to produce organic acids. It is concluded that local A2 isolate (B. borstelensis) produces mannanase which can be used to produce prebiotics from PKC.